1997
DOI: 10.1111/j.1600-0447.1997.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific P300 features in patients with cycloid psychosis

Abstract: In previous studies, low amplitudes and asymmetrical topography with right-sided peaks of the P300-evoked response have been repeatedly described in schizophrenic patients. A sample consisting of 18 patients with cycloid psychosis fulfilling the criteria of Perris and Brockington and 18 controls was investigated with a standard auditory odd-ball paradigm and multichannel evoked potential recordings. Patients had normal P300 topographies and latencies but significantly higher amplitudes than the controls. Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 23 publications
3
8
2
1
Order By: Relevance
“…A twin study that used Leonhard’s classification to compare concordance rates in monozygotic and dizygotic twins for each class of psychoses found much lower genetic load for cycloid psychoses and systematic schizophrenias as compared to unsystematic schizophrenia [36]. Another study found no reduction in P300 amplitudes in patients with cycloid psychoses as compared to healthy controls [37]. These results indicated that P300 amplitudes were spared in psychoses with lower genetic loadings and our results are consistent with this indication.…”
Section: Discussionsupporting
confidence: 82%
“…A twin study that used Leonhard’s classification to compare concordance rates in monozygotic and dizygotic twins for each class of psychoses found much lower genetic load for cycloid psychoses and systematic schizophrenias as compared to unsystematic schizophrenia [36]. Another study found no reduction in P300 amplitudes in patients with cycloid psychoses as compared to healthy controls [37]. These results indicated that P300 amplitudes were spared in psychoses with lower genetic loadings and our results are consistent with this indication.…”
Section: Discussionsupporting
confidence: 82%
“…Duncan et al (Strik et al 1994) in 1987 described an increase in P300 amplitudes after successful treatment in the patients with ATPD, and no correlation between P300 amplitudes and neuroleptic dosages was found. The finding of higher-than-normal amplitudes in cycloid psychosis was consistent in different studies (Strik et al 1994(Strik et al , 1997Pfefferbaum et al 1989;Duncan et al 1987), and this group typically had an excellent prognosis in form of full recovery and complete restitution of social competence. As the P300 amplitudes correlate with attentional performance and with higher levels of norepinephrine metabolite in CSF, it was proposed that higher-than-normal amplitudes might be an indication of higher levels of arousal in the cycloid psychosis group (Strik et al 1997).…”
Section: Neurophysiological Basissupporting
confidence: 51%
“…Among the somatic factors, early exposure to gestational infections (first trimester) and other obstetric complications are worth mentioning (Stöber 2005). Studies of event-related potentials revealed distinct characteristics in cycloid psychoses, but there have yet been only two neuroimaging studies explicitly investigating functional correlates of cycloid psychoses, suggesting a global ''hyperactivity'' during the phasic occurrence of cycloid psychoses favouring occipital on cost of frontal perfusion, particularly on the right side of the brain, whereas ''acute hyperfrontality'' is redistributed to occipito-temporo-parietal areas upon their treatment and remission (Strik et al, 1996;Jabs et al 2002). The systematic schizophrenias are the most debilitating schizophrenic diseases with distinct clinical pictures pointing to specific circumscribed functional psychic fields, so that in each subtype a definite higher function of the nervous system is involved.…”
Section: Subphenotypesmentioning
confidence: 99%